Influence of tide variations on the emergences of Caretta caretta in the island of Boavista (Cape Verde islands, Western Africa) - Madariaga, Begoña; Díaz Merry, A.; Ordi, D. del; López, Óscar; Ballell-Valls, Lluis; Abella Pérez, Elena; Gracia, M., Borrás, S.; Herraiz, L.; Cejudo, Daniel; Varo-Cruz, Nuria; López-Jurado, Luis Felipe (2017)
The island of Boavista (Republic of Cape Verde, Western Africa) is located in front of Senegal (Fig. 1). Here we find one of the most important nesting colonies of Caretta caretta in North Atlantic Ocean (López-Jurado and Andreu 1998). Reproduction biology of this population is been a part of a conservation effort since 1998. Although the relationship between tides and emergences of sea turtles follows a pattern that depends on several factors as the slope of the beach (Frazer 1983, Le Buff 1990) we have tried to determine, as a preliminary approach, if the emergences of loggerheads in Boavista are influenced by the tidal stage, independently of the slope of the beach.